Business process modelling linguistic approach application in public administration (self-governmental). (2018) - Stašák, Jozef; Schmidt, Peter
The paper deals with an application of a linguistic approach to business process modelling implemented and operated within self-governmental institutions. The administration is considered to be the core process and the records management is denoted as the main process and a subject to be modelled, while a set of adequate rules and principles postulated via Ministry of Interior of the Slovak Republic are being respected, when providing those activities. The paper's theoretical part deals with explanation of terms and principles important for the above-mentioned type of modelling. The second paper's part which deals with practical aspects is concerned with records management business process linguistic modelling. Both of the above-mentioned parts create an integral part of records management expert system: (ES-RM) conceptual model, which creates basis adequate application programs, and should enable the ES-RM implementation and operation in practice.